The implementation of total quality management at vocational high schools in Indonesia - Felestin, Felestin; Triyono, Mochamad Bruri (REID (Research and Evaluation in Education), 2015)
This study aims to determine the implementation of Total Quality Management (TQM) in public and private vocational high schools in the city of Yogyakarta, as well as to compare the level of implementation between public and private vocational high schools. The TQM aspects observed include infrastructures and facilities, quality of improvement, quality of teachers, quality of examination system and academic background of teachers graduated from vocational high schools. This exploratory study is descriptive in which the result can be used as an input as well as improvements in reflection of the future. These subjects were teachers and students. The primary data were collected through a questionnaire while other data were collected through observation and interviews. The data were analyzed by means of descriptive and statistics t-test. The analysis finds that TQM has been implemented by vocational schools, public and private, in the city of Yogyakarta. The Application levels differed significantly (t-value = 9.204, p-value = <0.0001), where the public schools are able to implement at a very good level, while private schools are at a good level. The differences in the application of TQM occur in all measurable aspects, namely infrastructures and facilities access, quality of improvement, quality of teachers, quality of examination system and academic background of teachers graduated from vocational high schools. Specifically, on aspects of infrastructures and facilities of the access, although on average they significantly differ, categorically they are in the same level.  The differences are not too large. The result of observation in the field during the study shows that the state vocational already maximally implement TQM, while in the private vocational schools, it is lower due to the limited resources in private schools.